PENGGUNAAN MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN TENTANG NILAI-NILAI PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS V SD NEGERI NUNUFAFI KABUPATEN TIMOR TENGAH UTARA - Naitili, Kriswinda; Taneo, Silvester P.; Kota, Martha K. (SINERGI : Jurnal Riset Ilmiah, 2024)
This study aims to improve learning outcomes in learning about Pancasila values ​​using the Problem Based Learning (PBL) model in Class V of Nunufafi Elementary School, TTU Regency. The type of research used is classroom action research with stages, namely planning, implementation, observation, testing and reflection by taking the research location at Nunufafi Elementary School, TTU Regency. he subjects of this study were 14 class V students consisting of 10 boys and 4 girls. Data collection was carried out using observation and test techniques, the data that had been collected was processed and analyzed further using qualitative descriptive analysis. Student learning outcomes increased from cycle I to cycle II, namely the learning outcomes of cycle I can be seen that out of 14 students who completed 5 people (35.71%) with sufficient criteria and increased in cycle II, namely 13 people (92.85%) with very good criteria. Based on the results of the research and discussion, it can be concluded that the use of the Problem Based Learning (PBL) model can improve student learning outcomes on the material on the richness of Pancasila values ​​in class I V of Nunufafi Elementary School, TTU Regency.